PENGARUH IKLIM ORGANISASI DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI RUMAH SAKIT DR. MOEWARDI SURAKARTA - MASNURHADI, MASNURHADI (2005)

(untitled)
The purpose of this study is to show the influence of organization atmosphere and compensation to work productivity. The model has been examined in Dr. Moewardi Hospital Surakarta. The model placed organization atmosphere and compensation as independent variable, and work productivity as dependent variable. Data has been collected from respondents of this research are the employee in Dr. Moewardi Hospital Surakarta. The number of sample is 64 person that be drawn by stratified random sampling. The analysis mainly based on Ordinary Least Square (OLS). Regression result also examined with normality test, heteroscedasticity test, autocorrelation test, and multicolinearity test. Result of this study proved that variable of organization atmosphere has positive and significant influence to work productivity. Variable of compensation has positive and significant influence to work productivity. The test of classical assumption show that spread of data have normal, and haven't heteroscedastic, autocorrelation, and multicolinearity. It was conclude that OLS method are fit enough as tools of analysis.